Spatiotemporal-controllable ROS-responsive camptothecin nano-bomb for chemo/photo/immunotherapy in triple-negative breast cancer - Wenjie Xu; Zhaokui Zeng; Yucheng Tang; Jingjing Tian; Xinyan Hao; Pengcheng Sun; Yanjin Peng; Tian Tian; Daxiong Xiang; Rongrong Wang; Chuanpin Chen; Junyong Wu (Journal of Nanobiotechnology)
Abstract Chemotherapy is still one of the major approaches in triple-negative breast cancer (TNBC) treatment. The development of new formulations for classic chemotherapeutic drugs remains interests in studies. Camptothecin (CPT) is powerful antitumor agents in TNBC treatment though its clinic applications are limited by its low water solubility and systemic toxicity. To prepare a spatiotemporal controllable CPT nano-formulation, we construct a ROS-responsive self-assembly nanoparticle by combining hydrophobic CPT and hydrophilic 5-floxuridine (FUDR). A ROS-sensitive thioketal (TK) linker is used to prepare CPT-TK-FUDR (CTF). Next, we introduced IR780-based phototherapy to elicit massive ROS regeneration due to the endogenous ROS is not sufficient. IR780 is modified with hyaluronic acid (HA) to prepare HA-modified IR780 (HAIR) for its biocompatibility and tumor targeting ability improvement. CTF and HAIR self-assemble to form an attractive nano-bomb (HAIR/CTF NPs). HA accurately guides the NPs to tumor sites via HA-receptor recognition on tumor cells. After internalization, overexpressed intracellular HAase in tumor cells disassembles the NPs to free the contents. Due to the presence of IR780 molecules, the scheduled irradiation of 808 nm laser induces massive reactive oxygen species (ROS) generation, which further result in the cleavage of TK linker for free drugs release. Additionally, ROS-mediated photodynamic therapy (PDT) and near-infrared laser-mediated photothermal therapy (PTT) synergistically worked to eradicate tumor cells. Then immunogenic cell death (ICD) was evoked by CPT and phototherapy to amplify antitumor immunity, thereby achieving primary and abscopal tumor inhibition. In conclusion, the HAIR/CTF nano-bomb realized spatiotemporal controllable drug release, exciting tumor eradication and attractive anti-metastasis efficacy via combination chemo/photo/immunotherapy, offering a valuable reference for the re-development of classic drug in future clinical practice. Graphical Abstract